Running Your Best Triathlon Race - Etxebarria, N.; Wright, J.; Jeacocke, H.; Mesquida, C.; Pyne, D. B. (International Journal of Sports Physiology and Performance, 2021)
Negative or evenly paced racing strategies often lead to more favorable performance outcomes for endurance athletes. However, casual inspection of race split times and observational studies both indicate that elite triathletes competing in Olympic-distance triathlon typically implement a positive pacing strategy during the last of the 3 disciplines, the 10-km run. To address this apparent contradiction, the authors examined data from 14 International Triathlon Union elite races over 3 consecutive years involving a total of 725 male athletes. Analyses of race results confirm that triathletes typically implement a positive running pace strategy, running the first lap of the standard 4-lap circuit substantially faster than laps 2 (~7%), 3 (~9%), and 4 (~12%). Interestingly, mean running pace in lap 1 had a substantially lower correlation with 10-km run time (r = .82) than both laps 2 and 3. Overall triathlon race performance (ranking) was best associated with run performance (r = .82) compared with the swim and cycle sections. Lower variability in race pace during the 10-km run was also reflective of more successful run times. Given that overall race outcome is mainly explained by the 10-km run performance, with top run performances associated with a more evenly paced strategy, triathletes (and their coaches) should reevaluate their pacing strategy during the run section.